Traditional Indian Herb Emblica Officinalis & Its Medicinal Importance - Jain, Pushpendra Kumar; Das, Debajyoti; Pandey, Nalini; Jain, Prachi (Innovare Journal of Ayurvedic Sciences, 2016)
Emblica Officinalis (Amla, EO and E. officinalis) is one of the most important herbs in the Indian traditional medicine system, especially Ayurveda and also known as King of all medicinal plants. Emblica officinalis is famous Ayurvedic herb (the name means sour in Sanskrit) is one of the most useful medicines in the Indian pharmacopoeia, and is considered to be one of the strongest uvenatives (Rasayana), particularly for the blood, bones, liver and heart. It is an exceptionally rich source of vitamin C containing thirty times the amount found in oranges. It is one of the oldest oriental medicines mentioned in Ayurveda as potential remedy for various ailments. Emblica officinalis (Amla) is widely used in the ayurvedic medicines and believed to increase defense /immune power against diseases. Several parts of the plant are used to treat a variety of diseases, but the most important is the fruitâ€. The fruit is rich in quercetin, phyllaemblic compounds, gallic acid, tannins, flavonoids, pectin and vitamin C and also contains various polyphenolic compounds. A wide range of phyto-chemical components including terpenoids, alkaloids, flavonoids, and tannins have been shown to posses' useful biological activities. Many pharmacological studies have demonstrated the ability of Emblica officinalis as antioxidant, anticarcinogenic, antitumour, antigenotoxic, antiinflammatory activities, anticancer, anti HIV-reverse transcriptase, antidiabetic, antidepressant, antiulcerogenic, hair growth tonic, wound healing activities, cardiovascular diseases, neurodegenerative diseases, cancer and many other traditional uses of the plant. The present study also includes macroscopy, microscopy, preliminary Phyto-Constituent and Physico-chemical evaluation. Keywords: Amla, Emblica officinalis, Vitamin C, Ayurvedic Medicines, Hair Growth Tonic, Antioxidant, Anticancer, Phyto-Constituent, Physico-chemical, Macroscopy, Microscopy, Traditional Uses.